Structural Community Governance: Importance for Community‐Academic Research Partnerships. Issue 3 (23rd April 2021) - Sanchez‐Youngman, Shannon; Boursaw, Blake; Oetzel, John; Kastellic, Sara; Devia, Carlos; Scarpetta, Maia; Belone, Lorenda; Wallerstein, Nina
Abstract: Community based participatory research (CBPR) emphasizes democratic knowledge production and joint action between academics and communities to promote health equity through multilevel interventions. While much scholarship has expressed a commitment to collaboration between researchers and communities, effective methods of structural governance between community and academic stakeholders is under explored. We fill this gap by presenting a conceptual and empirical analysis describing multiple dimensions of structural governance in CBPR partnerships. First, we integrate public policy evidence on effective collaborative governance designs with the emerging literature in CBPR to create a conceptual model. Next, we utilize internet surveys of 179 federally funded community engaged research projects to construct and assess a measure of structural governance across multiple dimensions using confirmatory factor analysis. We explore whether antecedent factors such as the stage of the partnership and ethnic composition are associated with these dimensions and we examine associations for each of these components on positive perceptions of community involvement of research and collective empowerment. We develop a robust multidimensional measure of structural governance that is positively associated with perceptions of increased community involvement in research and collective empowerment. Highlights: We propose a conceptual model for structural governance in community based participatory research. The model measures community approvals, co-leadership, joint decision making, and resource sharing. Federally funded CBPR partnerships display moderate levels of structural governance. Structural governance is associated with community involved research and collective empowerment. Structural governance ensures community benefit to be at the forefront of CBPR.